Peran Guru Pendidikan Agama Islam dalam Membentuk Karakter Siswa di Era Digital - Mahesa, Eldyo; Hidayat, Syahril; Gusmaneli, Gusmaneli (Lembaga Yasin AlSys, 2025)
In the digital era marked by rapid advancements in information technology, character formation among students faces increasingly complex and multidimensional challenges. Within this context, Islamic Religious Education (PAI) teachers hold a strategic role in instilling moral and spiritual values that serve as the foundational pillars of student character. This study aims to analyze the contribution of PAI teachers in educating the younger generation to develop strong character, noble conduct, and the ability to filter negative influences arising from digital developments. The method employed is descriptive-qualitative with a literature review approach. The findings indicate that the role of PAI teachers extends beyond that of mere instructors; they also serve as role models, mentors, and facilitators who integrate Islamic values with digital literacy skills. This integration enables character education through PAI to function as both a preventive and constructive instrument in shielding students from moral crises brought about by digitalization. Thus, PAI teachers become key agents in promoting value-based character education that is responsive to the dynamics of the digital age.